Buried - La Plante, Lynda (La Plante, Lynda. DC Jack Warr, 2020)
DC Jack Warr and his girlfriend Maggie have just moved to London to start a new life together. Warr is drawn into an investigation that turns his life upside down. In the aftermath of a fire at an isolated cottage, a badly burned body is discovered, as well as the burnt remains of millions of stolen, untraceable bank notes. The search leads Warr deep into a murky underworld.